Perbandingan Tingkat Kefasihan Membaca Al-Qur’an Siswa Lulusan SDIT dengan Siswa Lulusan SD N Kelas VII MtsN 1 Kota Payakumbuh - Aisyah Raihan Fadilah; Darul Ilmi; Baihaqi Anas; Januar Januar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
There is a difference in the fluency in reading the Qur'an for class VII students at MTsN 1 Payakumbuh between SDN graduates and SDIT graduates. From the initial observations made, the authors found a temporary difference that students who graduated from SD N were more fluent in reading than students who graduated from SDIT. The problem that the author examines is how significant the difference in fluency in reading the Qur'an SDIT graduate students with SDN graduate students in class VII MTsN 1 Payakumbuh. And the aim is to find out how significant the differences in Al-Qur'an reading fluency are between IT Elementary School Graduates and Public Elementary School Graduates. This research uses a type of field research (field research) using a quantitative approach using a comparative descriptive design. Comparative research is a type of research that aims to compare the presence of one or more variables in two or different samples or at different times. The sample that the researcher used was several grade VII students who graduated from SDN and SDIT. The data collection techniques that the researchers used were oral tests and documentation. From the results of the data analysis used to test the hypothesis using the Mann-Whitney Test because the data is not normally distributed and not homogeneous and the results of statistical tests show that the Asymp.Sig.(2-tailed) value is .031 so it can be concluded that it is .031 < 0.05 and the hypothesis is accepted. If the hypothesis is accepted, it means that there is a significant difference in Al-Qur'an Reading Fluency between Elementary School Graduates and Elementary School IT Grade VII Students at MTsN 1 Payakumbuh City. Where students who graduated from SD N are more fluent in reading the Al-Qur'an than students who graduated from SD IT.